Electrochemical remediation of industrial pharmaceutical wastewater containing hormones in a pilot scale treatment system - Lima Morais, Ruiter; Ferreira Garcia, Luane; Kussmaul Gonçalves Moreno, Emily; Vieira Thomaz, Douglas; de Brito Rodrigues, Laís; Barroso Brito, Lara; Sanz Lobón, Germán; Augusto Rodrigues de Oliveira, Gisele; Ferreira Rodrigues, Marcella; Gontijo Vaz, Boniek; Gil, Eric de Souza (Eclética Química, 2019)
The elimination of residual drugs from pharmaceutical and domestic sources is a growing concern, as they are able to reach water and soil resources and can present environmental and health risks even in very low concentrations. Traditional water and wastewater treatment systems have not been efficient in the removal of these compounds, evidencing the importance of the development of new remediation methods. In view of the applicability and versatility of electrocoagulation techniques in the removal of pollutants, the aim of this work is to evaluate the parameters: biochemical oxygen demand (BOD), chemical oxygen demand (COD), color, turbidity, algestone acetophenide (AAc) and estradiol enanthate (EEn) using a pilot treatment system, as well as phytotoxicity and Brine shrimp toxicity. The study showed good removal efficiency, comprising remarkable remediation performance assayed through BOD (61.5%), COD (58.6%), color (83.1%), turbidity (96.7%), AAc (77.0%) and EEn (56.7%) after 30 minutes. For toxicity, raw effluent was considered more phytotoxic for lettuce and cucumber seeds when compared to treated effluent. The results suggest that the pilot prototype was promising, providing an increase in both the germination potential and the root growth of the seeds (Lactuca sativa and Cucumis sativus) and a significant decrease in the acute toxicity to Artemia salina.